Nanofiber Scaffolds as Drug Delivery Systems to Bridge Spinal Cord Injury - Angela Faccendini; Barbara Vigani; Silvia Rossi; Giuseppina Sandri; Maria Cristina Bonferoni; Carla Marcella Caramella; Franca Ferrari (MDPI AG, 2017)
The complex pathophysiology of spinal cord injury (SCI) may explain the current lack of an effective therapeutic approach for the regeneration of damaged neuronal cells and the recovery of motor functions. A primary mechanical injury in the spinal cord triggers a cascade of secondary events, which are involved in SCI instauration and progression. The aim of the present review is to provide an overview of the therapeutic neuro-protective and neuro-regenerative approaches, which involve the use of nanofibers as local drug delivery systems. Drugs released by nanofibers aim at preventing the cascade of secondary damage (neuro-protection), whereas nanofibrous structures are intended to re-establish neuronal connectivity through axonal sprouting (neuro-regeneration) promotion, in order to achieve a rapid functional recovery of spinal cord.